2000
DOI: 10.1046/j.1365-2567.2000.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Recessive expression of the H2A‐controlled immune response phenotype depends critically on antigen dose

Abstract: SUMMARYMajor histocompatibility complex (MHC) alleles acting as immune response genes are coexpressed in heterozygous individuals and therefore control of immune responses is usually codominant. As an exception to this rule, however, several examples of recessive immune responses have been ascribed to regulatory, e.g. suppressive, interactions. We report here that the recessive phenotype of both antibody and T-cell responses to the mycobacterial 16 000-MW antigen depends critically on a low antigen dose for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Competition ELISA showed that whereas an IgG anti-Acr mAb (TBG65) inhibited binding of TBA61 to Acr-coated plates, 2E9IgA1 did not (data not shown). Moreover, 2E9IgA1 and TBA61 bound to different, partly overlapping, truncated Acr recombinants, and neither bound linear peptides of Acr (28) (data not shown). We conclude that 2E9IgA1 and TBA61 recognize different (yet structurally undefined) epitopes on Acr.…”
Section: Resultsmentioning
confidence: 94%
“…Competition ELISA showed that whereas an IgG anti-Acr mAb (TBG65) inhibited binding of TBA61 to Acr-coated plates, 2E9IgA1 did not (data not shown). Moreover, 2E9IgA1 and TBA61 bound to different, partly overlapping, truncated Acr recombinants, and neither bound linear peptides of Acr (28) (data not shown). We conclude that 2E9IgA1 and TBA61 recognize different (yet structurally undefined) epitopes on Acr.…”
Section: Resultsmentioning
confidence: 94%
“…Though this model of selective multibacillary lung disease seems relevant, the antigen specificity of the underlying immune responses was not identified. Although antibody responses to different antigens and epitopes is under H-2A control following immunization with soluble antigens in adjuvants ( 84 , 85 ), there is no clear corresponding evidence following Mtb infection. On the other hand, antibody responses to hsp65 and hsp71 antigens ( 86 ) and liver granuloma formation ( 87 ) following Mtb infection were associated with non-H-2 genes.…”
Section: Association Of Hla-dr and Antibody Epitope Specificity With mentioning
confidence: 99%
“…Many immunogenetic factors are associated with host immune responses and susceptibility to M.tb in mice [37], including the major histocompatibility (MHC) haplotype (known as the H-2 haplotype in mice) [814]. A direct relationship between H-2 k and increased susceptibility to M.tb has been established, whereby the H-2 k alleles reduced survival of BALB/c H-2 k congenic mice following aerosol infection [9] and impaired the control of M.tb growth in the lungs following intraperitoneal infection [15].…”
Section: Introductionmentioning
confidence: 99%